Escitalopram enhances synchrony of brain responses during emotional narratives in patients with major depressive disorder - Komulainen Emma; Glerean Enrico; Heikkilä Roope; Nummenmaa Lauri; Raij Tuukka T.; Isometsä Erkki; Ekelund Jesper (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2025)
One-week treatment with escitalopram decreases amygdala responses to fearful facial expressions in depressed patients, but it remains unknown whether it also modulates processing of complex and freely processed emotional stimuli resembling daily life emotional situations. Inter-subject correlation (ISC) offers a means to track brain activity during complex, dynamic stimuli in a model-free manner.& nbsp; Twenty-nine treatment-seeking patients with major depressive disorder were randomized in a double-blind study design to receive either escitalopram or placebo for one week, after which functional magnetic resonance imaging (fMRI) was performed. During fMRI the participants listened to spoken emotional narratives. Level of ISC between the escitalopram and the placebo group was compared across all the narratives and separately for the episodes with positive and negative valence.& nbsp; & nbsp;Across all the narratives, the escitalopram group had higher ISC in the default mode network of the brain as well as in the fronto-temporal narrative processing regions, whereas lower ISC was seen in the middle temporal cortex, hippocampus and occipital cortex. Escitalopram increased ISC during positive parts of the narratives in the precuneus, medial prefrontal cortex, anterior cingulate and fronto-insular cortex, whereas there was no significant synchronization in brain responses to positive vs negative events in the placebo group. Increased ISC may imply improved emotional synchronization with others, particularly during observation of positive events. Further studies are needed to test whether this contributes to the later therapeutic effect of escitalopram.